The message of 2 Timothy guard the gospel - Stott, John Robert Walmsley, 1921- (Leicester, UK IVP, 1973)
Includes bibliographical references.
"The Bible speaks today series has been placed in the library in memory of Gordon W. Craig, 1926-1990". Originally published under the title "Guard the gospel".
Keywords: Bible. N.T. Timothy, 2nd -- commentaries